Development of a Density Gauge for Measuring Water and Mud Density based on a Radioactive Technique - Aloysius Bagyo Widagdo (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2022)
The density or concentration of mud is one of the key variables in studying cohesive sediments, due to being accumulated through settlement and consolidation, as well as resuspended through erosion. This indicates that the proper measurement of sediment density is important. Therefore, this study aims to evaluate the accuracy of density measurement by using the gamma-ray attenuation method as a non-intrusive technique. For Compton Scattering, gamma-ray attenuation was effectively independent of mineralogy, subsequently depending on only the electron density of the material, which is directly related to the bulk density of the mixture. Based on the results, the advantages of utilizing the nucleonic density gauge indicated that the technique was non-intrusive and very flexible for many experimental arrangements, as well as the high accuracy of measurements with errors less than 1%.